Childhood Malnutrition and Its Determinants among Under‐Five Children in Ghana. Issue 6 (1st September 2015) - Aheto, Justice Moses K.; Keegan, Thomas J.; Taylor, Benjamin M.; Diggle, Peter J.
Abstract Background Childhood malnutrition adversely affects short‐ and long‐term health and economic well‐being of children. Malnutrition is a global challenge and accounts for around 40% of under‐five mortality in Ghana. Limited studies are available indicating determinants of malnutrition among children. This study investigates prevalence and determinants of malnutrition among children under‐five with the aim of providing advice to policymakers and other stakeholders responsible for the health and nutrition of children. Methods The study used data from the 2008 Ghana Demographic and Health Survey (GDHS). Analyses were conducted on 2083 children under 5 years old nested within 1641 households with eligible anthropometric measurements, using multilevel regression analysis. Results from the multilevel models were used to compute probabilities of malnutrition. Results This study observed that 588 (28%), 276 (13%), and 176 (8%) of the children were moderately 'stunted', moderately 'underweight', and moderately 'wasted' respectively. Older ages are associated with increased risk of stunting and underweight. Longer breast‐feeding duration, multiple births, experience of diarrhoeal episodes, small size at birth, absence of toilet facilities in households, poor households, and mothers who are not covered by national health insurance are associated with increased risk of malnutrition. Increase in mother's years of education and body mass index are associated with decreased malnutrition. Strong residual household‐level variations in childhood nutritional outcomes were found. Conclusion Policies and intervention strategies aimed at improving childhood nutrition and health should address the risk factors identified and the need to search for additional risk factors that might account for the unexplained household‐level variations.